2007
DOI: 10.4161/cc.6.18.4707
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Derived Cells and Alternative Pathways of Oogenesis in Adult Rodents

Abstract: Oocyte generation in adult mouse ovaries by putative germ cells (PGCs) in bone marrow and peripheral blood has recently been proposed. It, however, remains unclear whether in laboratory rodents the PGCs reside in BM or the BM cells stimulate oogenesis from ovarian stem cells. We utilized immunoperoxidase staining to localize PGCs, oocytes, and BM derived cells in ovaries of adult (age 45-60 days) control and neonatally estrogenized rat females. In controls, BM derived cells accompanied emergence of PGCs from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(53 citation statements)
references
References 8 publications
(19 reference statements)
1
52
0
Order By: Relevance
“…Regarding the argument (2) that OSC are not essential for neo-oogenesis since the oocytes persist in ovaries lacking OSC, we demonstrated that in rat ovaries lacking OSC the oocytes originate by an alternate pathway, from medullary somatic stem cells, and primordial follicles are formed in the juxtaposed deep ovarian cortex (Bukovsky et al, 2007).…”
Section: The Oocyte Storage Versus Continued Formation Conceptmentioning
confidence: 84%
See 4 more Smart Citations
“…Regarding the argument (2) that OSC are not essential for neo-oogenesis since the oocytes persist in ovaries lacking OSC, we demonstrated that in rat ovaries lacking OSC the oocytes originate by an alternate pathway, from medullary somatic stem cells, and primordial follicles are formed in the juxtaposed deep ovarian cortex (Bukovsky et al, 2007).…”
Section: The Oocyte Storage Versus Continued Formation Conceptmentioning
confidence: 84%
“…In fetal ovaries, with the support of the immune system related cells, secondary germ cells arise from the somatic OSC. The OSC have been implicated in the formation of oocytes (Allen, 1923;Evans and Swezy, 1931;Everett, 1943;Bukovsky et al, 1995;Bukovsky et al, 2004;Bukovsky et al, 2007), and it also has been suggested that they are a source of granulosa cells (Brambell, 1927;Motta et al, 1980;Bukovsky et al, 1995;Bukovsky et al, 2004;Bukovsky et al, 2005a). As already indicated, numerous small germ cells (10 lm in diameter) are present in OSC layer of human fetal ovaries from 7 to 24 weeks of intrauterine life (Motta and Makabe, 1986).…”
Section: Establishment Of Osc Niche In Embryonic Ovariesmentioning
confidence: 98%
See 3 more Smart Citations